2003
DOI: 10.1034/j.1600-0765.2003.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin release from human neutrophils is induced by Porphyromonas gingivalis lipopolysaccharide via the CD‐14–Toll‐like receptor–nuclear factor κB pathway

Abstract: These results suggest that calprotectin release is induced by P-LPS via the CD14-TLR2-NF-kappaB signal pathway in human neutrophils and may be dependent on microtubule and microfilament systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 38 publications
2
60
0
Order By: Relevance
“…Kaner et al [44] have demonstrated that GCF calprotectin levels are significantly correlated with the levels of periodontal inflammation and decreased after periodontal therapy in G-AgP patients. Elevated GCF calprotectin levels in diseased groups might be due to the increased activation of inflammatory cells by bacterial components as well as greater release of intracellular material in gingivitis and periodontitis [45][46][47]. As a result, calprotectin could contribute to the host inflammatory immune defense against bacteria in periodontal disease [8,9,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Kaner et al [44] have demonstrated that GCF calprotectin levels are significantly correlated with the levels of periodontal inflammation and decreased after periodontal therapy in G-AgP patients. Elevated GCF calprotectin levels in diseased groups might be due to the increased activation of inflammatory cells by bacterial components as well as greater release of intracellular material in gingivitis and periodontitis [45][46][47]. As a result, calprotectin could contribute to the host inflammatory immune defense against bacteria in periodontal disease [8,9,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, intestinal epithelial cells were shown to be broadly unresponsive to commensals (i.e., TLR2 ligands), secondary to deficient expression of TLR2 and TLR6 and increased expression of Tollip (a TLR-inhibitory protein) (26). Evidence that P. gingivalis resembles a commensal clonally (23,27) and expresses an LPS with low endotoxin activity that targets primarily TLR2 (15,16,21,24) suggests the intriguing possibility that this pathogen may survive in the oral cavity by posing as a commensal, evocative of gut commensals.…”
Section: Vol 73 2005 Oral Mucosal Endotoxin Tolerance 691mentioning
confidence: 99%
“…In short, P. gingivalis more closely resembles an opportunist (23) or commensal (27) than a pathogen. Moreover, P. gingivalis bears an LPS (PgLPS) with low endotoxin activity that primarily targets the "commensal receptor" TLR2 (15,16,21,24) but also has activity for TLR4 (4,10). PgLPS induces a predominant T H 2-type immune response in vivo (33) and in vitro (18), and one report suggests that PgLPS can induce immune tolerance in vitro (5).…”
Section: Introductionmentioning
confidence: 99%
“…These include periodontitis; Porphyromonas gingivalis LPS promotes S100A8/A9 release from human neutrophils via a CD14-TLR2-NF-κB pathway. 33 Arthropathies, including rheumatoid arthritis (RA) and systemic lupus erytheal 11 ]) in the circulation with clinical activity of numerous inflammatory diseases. 12-14 Unlike S100A8 and S100A9, there is no S100A12 in rodent genomes; human S100A12 lies between S100A8 and S100A9 in a subcluster of S100 genes on chromosome 1q21 and is structurally similar to these.…”
Section: Calgranulins In Diseases Predisposing To Cardiovascular Riskmentioning
confidence: 99%